The impacts of reforming agricultural policy support on cereal prices: a CGE modeling approach - Valera, Harold Glenn A.; Bharathi, Sindhu; Balie, Jean; Pede, Valerien O.; Chakravarthy, Sumathi; Gopalakrishnan, Badri (Emerald Publishing Limited, 2024)
The scientific debate on what constitutes a healthy diet and what constitutes a sustainable food system is heated and unresolved. In this context, it is important to investigate a specific question which relates to the food price outlook, particularly for cereals. This paper examines the effects of the expected reforms of agricultural support policies on cereal prices in several countries. In doing so, we simulate a scenario on the total abolition of all agricultural subsidies using the GTAP model and focus on 27 countries and 7 regional aggregates. We consider two alternative scenarios: (1) removal of subsidies on (a) output, (b) primary input, (c) domestic intermediate input, and (d) imported intermediate input in all agricultural sectors; (2) removal of border tariffs in all agricultural sectors. The simulation results suggest that the removal of agricultural subsidies would increase the price of cereals in all of the sample countries.